Penyaluran Bantuan Korban Bencana Alam Studi Kasus Pemulihan Kehidupan Korban Bencana Alam di Kota Jayapura - Akhmad Purnama; Murdiyanto Murdiyanto (Jurnal Penelitian Kesejahteraan Sosial, 2013)
Appropriate natural disaster victims aid distribution is an effort to reduce more victims, the problem of aid distribution are so many refugees camps and coordination among command posts. In an effort to know aid distribution, especially in Jayapura Municipality, this research is done. The research question is how aid distribution for natural disaster victims implemented and what are the supporting and handicap factor in this distribution? The answer is the goal of the research. The research location is ditermined purposively based on its most natural disaster happening frequency, sort of earthquake, flood, landslide, and tsunami. Information resources (informant) taken from distribution aparatus, victims, and people who know directly on natural disaster. Informants are choosen purposively with the4 cosideration that those know well about disasterÂ in their place and having formal and informal competency in the case. Date are gathered through interview, observation, documentary analysis, and focus group discussion. Data are analysed through qualitative-descriptive technique. The research finds that the implementation of natural disaster aid distribution is done swiftly, because of many supports from natural disaster prevention, social, health, military district, police district, ready disaster youth, and volonteers in under district, district, municipality, and province level that are implemented well and solidly. The handicap factors are the unadequate of land and water transportation devices that make the distribution arriving late. Aid distribution mostly fulfilled, such as health services, home and environmental rehabilitation, working and bussines rehabilitation. One that is unfulfield yet is the living resources of fishermen, such as boat for fishing as dailly lives resouces. It is recommended that transportation devices should be completed both for land and water needs, so that rehabilitation program can be fully realized for the victims that mostly fishermen to activate their work to fulfilled their daily lives needs.